Quantitative in situ XRD measurement of shock metamorphism in Martian meteorites using lattice strain and strain‐related mosaicity in olivine. (6th February 2019) - Jenkins, Laura E.; Flemming, Roberta L.; M Causland, Phil J. A.
Abstract: All Martian meteorites have experienced shock metamorphism to some degree. We quantitatively determined shock‐related strain in olivine crystals to measure shock level and peak shock pressure experienced by five Martian meteorites. Two independent methods employing nondestructive in situ micro X‐ray diffraction (μXRD) are applied, i.e., (1) the lattice strain method, in which the lattice strain value (ε) for each olivine grain is derived from a Williamson–Hall plot using its diffraction pattern (peak width variation with diffraction angle) with reference to a best fit calibration curve of ε values obtained from experimentally shocked olivine grains; (2) the strain‐related mosaicity method, allowing shock stage to be estimated by measuring the streaking along the Debye rings of olivine grain diffraction spots to define their strain‐related mosaic spread, which can then be compared with olivine mosaicity in ordinary chondrites of known shock stage. In this study, both the calculated peak shock pressures and the estimated shock stages for Dar al Gani 476 (45.6 ± 0.6 GPa), Sayh al Uhaymir 005/8 (46.1 ± 2.2 GPa), and Nakhla (18.0 ± 0.6 GPa) compare well with literature values. Formal shock assessments for North West Africa 1068/1110 (53.9 ± 2.1 GPa) and North West Africa 6234 (44.6 ± 3.1 GPa) have not been reported within the literature; however, their calculated peak shock pressures fall within the range of peak shock pressures defining their estimated shock stages. The availability of nondestructive and quantitative μXRD methods to determine shock stage and peak shock pressure from olivine crystals provides a key tool for shock metamorphism analysis.